Polymorphisms in detoxification genes CYP1A1, CYP2E1, GSTT1 and GSTM1 in gastric cancer susceptibility. - González, Auxiliadora (2004)
Cytochrome P450 (CYP) and glutathione S-transferase (GST) enzymes are involved in activation and detoxification of many potential carcinogens. Genetic polymorphisms in those enzymes have been found to influence the interindividual susceptibility to cancer. Some polymorphisms of those enzymes have been associated specifically with susceptibility to gastric cancer. We conducted a study in a Costa Rican population, where gastric cancer incidence and mortality rates are among the highest in the world. We investigated whether such variations affected the risk of developing gastric cancer. Subjects included 31 with gastric cancer, 58 controls with gastric injures others than cancer and 51 normal controls confirmed by X-rays (double-contrast) or endoscopic diagnostic. DNA from peripheral white blood cell was obtained from all subjects. Deletion of GSTT1 and GSTM1 was assessed by multiplex PCR and genotyping of CYP2E1 was performed using a PCRbased restriction fragment length polymorphism assay with the restriction enzyme PstI and the gene CYP1A1 using the restriction enzyme MspI. The prevalence of CYP1A1 MspI polymorphism, GSTT1 and GSTM1 null genotype was similar in the three groups of individuals (p=0.73, p=0.88 y p= 0.89 respectively). Our findings suggest that the polymorphism CYP2E1 PstI could be associated with a reduced risk of having gastric cancer (OR=0.09, IC95%:0.01 - 0.83).